Sursele Bibliei de la Sankt Petersburg (1819) – o abordare comparativă - Veronica OLARIU (Philologia)
This study focuses on the third Romanian version of the biblical text, published in Saint Petersburg in 1819 with the support of the Russian Bible Society. Its objective is a comparative philological approach to the main Romanian versions of the biblical text (the Blaj Bible, 1795; the Bucharest Bible, 1688; Manuscript 45, preserved at the Cluj-Napoca branch of the Romanian Academy; Manuscript 4389 from the Romanian Academy Library) to establish their filiative relationships with the Saint Petersburg version. The use of the comparative-historical method aims to highlight this text, attempting to determine the extent to which the Saint PetersburgBible is a faithful rendition of the BlajBible or represents a version of its own identity within the Romanian biblical tradition.